Classification and molecular characteristics of tet(X)-carrying plasmids in Acinetobacter species - Chen, Chong; Huang, Ping-Yu; Cui, Chao-Yue; He, Qian; Sun, Jian; Liu, Ya-Hong; Huang, Jin-Lin (Frontiers in Microbiology, 2022)
The rapid dissemination of plasmid-mediated tet(X) genes in Acinetobacter species has compromised the clinical effectiveness of tigecycline, one of the last-resort antibiotics. However, the classification strategy and homology group of tet(X)-positive Acinetobacter spp. plasmids remain largely unknown. In this study, we classified them by genome-based replicon typing, followed by analyses of structural characteristics, transferability and in vivo effect. A total of 34 plasmids distributed in at least nine Acinetobacter species were collected, including three tet(X3)-positive plasmids and one tet(X6)-positive plasmid from our genome sequencing results. Among them, there were 28 plasmids carrying Rep_3 superfamily replicase genes and classified into six homology groups, consisting of GR31 (82.1%), GR26 (3.6%), GR41 (3.6%), GR59 (3.6%), and novel groups GR60 (3.6%) and GR61 (3.6%). Our tet(X3)-positive plasmids pYH16040-1, pYH16056-1 and pYH12068-1 belonged to the dominant GR31 group, whereas the tet(X6)-positive plasmid pYH12068-2 was unclassified. Structurally, all tet(X)-positive GR31 plasmids shared similar plasmid replication (repB), stability (parA and parB) and accessory modules (tet(X) and sul2), and 97.6% of plasmid-mediated tet(X) genes in Acinetobacter species were adjacent to ISCR2. Conjugation and susceptibility testing revealed pYH16040-1, pYH16056-1 and pYH12068-2, carrying plasmid transfer modules, were able to mediate the mobilization of multiple antibiotic resistance. Under the treatment of tigecycline, the mortality rate of Galleria mellonella infected by pYH16040-1-mediated tet(X3)-positive Acinetobacter spp. isolate significantly increased when compared with its plasmid-cured strain (p < 0.0001). The spread of such plasmids is of great clinical concern, more effects are needed and will facilitate the future analysis of tet(X)-positive Acinetobacter spp. plasmids.